Discovery of an LSD1 PROTAC degrader - Amir Hosseini; Xing Qiu; Yan Xiong; Ki Him Nicholas Chiang; Jerrel Catlett; Ines Kaltheuner; Zhijie Deng; Sudipta Ghosh; Yang Shi; Jian Jin (Proceedings of the National Academy of Sciences, 2025)
Aberrant expression of lysine-specific demethylase 1 (LSD1) has been implicated in various cancers, including acute myeloid leukemia (AML). Recent studies have revealed both catalytic and noncatalytic oncogenic functions of LSD1, which cannot be effectively addressed by traditional small-molecule inhibitors. Therefore, to remove LSD1 and mitigate its oncogenic activity, we utilized the proteolysis-targeting chimera (PROTAC) approach and developed an LSD1 PROTAC degrader MS9117, which recruits the E3 ligase cereblon (CRBN). MS9117 induces LSD1 degradation in a concentration-, time-, CRBN-, and proteasome-dependent manner. Importantly, MS9117 effectively degrades LSD1 and demonstrates superior antiproliferative effects in AML cells, compared to the existing pharmacological LSD1 inhibitors. Furthermore, MS9117 also sensitized nonacute promyelocytic leukemia AML cells to all-trans retinoic acid treatment. Moreover, we developed two negative controls of MS9117, MS9117N1 and MS9117N2, which do not degrade LSD1 or inhibit leukemia cell growth, further confirming the mechanism of action of MS9117. Overall, MS9117 serves as a valuable chemical tool and a potential therapeutic to target both the catalytic and scaffolding functions of LSD1. With several LSD1 inhibitors already in clinical development, the LSD1 degraders such as MS9117 offer an additional option for future clinical studies.